2022
DOI: 10.1007/s00417-022-05573-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peripheral refraction and higher-order aberrations between orthokeratology and multifocal soft contact lens designed with highly addition

Abstract: Purpose To compare peripheral defocus, higher-order aberrations (HOAs), and contrast visual acuity (CVA) in myopic children wearing orthokeratology (OK) lenses and multifocal soft contact lenses (MSCLs) designed with highly addition. Methods This is a prospective, nonrandomized, controlled study. Subjects at 8 to 13 years of age with spherical equivalent refraction from − 1.00 to − 5.00 dioptres (D) were included in the OK group (n = 30) and MSCL group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…39,42 Based on this mechanism, MFSCL and Ortho-K lenses might be expected to show similar trends in slowing myopia progression. Consistent with this hypothesis, our earlier findings 44 did indeed note that MFSCLs showed similar myopia control efficacy to Ortho-K. Therefore, our results suggest that the myopia control provided by MFSCLs would be more effective if the peak plus power was positioned closer to the pupil.…”
Section: F I G U R Esupporting
confidence: 91%
“…39,42 Based on this mechanism, MFSCL and Ortho-K lenses might be expected to show similar trends in slowing myopia progression. Consistent with this hypothesis, our earlier findings 44 did indeed note that MFSCLs showed similar myopia control efficacy to Ortho-K. Therefore, our results suggest that the myopia control provided by MFSCLs would be more effective if the peak plus power was positioned closer to the pupil.…”
Section: F I G U R Esupporting
confidence: 91%
“…43 Although peripheral VA was not measured in the present study, it can be speculated that the lenslets area would reduce peripheral VA. Further, OK lenses showed better peripheral visual performance than SVL in the superior visual field. Huang et al showed that the maximum peripheral defocus of OK lenses was +2.00 to +3.00 D at 10°-20° retinal eccentricity, 42 that is, lower than that for HAL and DISC lenses. On the other hand, it may be related to the way the lenses were used.…”
Section: Discussionmentioning
confidence: 97%
“…40 In addition, the peripheral defocus of HAL was the highest (+6.00 D) 41 among the three myopia prevention lenses. 27,42 Studies in both children and adults have found that the peripheral lenslets in the HAL significantly reduced central VA. 16,33 VA was best at the fovea and decreased gradually with increasing retinal eccentricity. 43 Although peripheral VA was not measured in the present study, it can be speculated that the lenslets area would reduce peripheral VA. Further, OK lenses showed better peripheral visual performance than SVL in the superior visual field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei dem Vergleich von multifokalen Linsen und Ortho‑K sind ferner verschiedene Faktoren und die individuelle Verträglichkeit zu berücksichtigen. Weiche multifokale Linsen sind mit einem größeren Defokus und schlechterem Kontrastsehen verbunden [ 47 ]. Die über Nacht getragenen Linsen können dagegen neben einer nachlassenden Myopiekorrektur und stärkeren Induktion von Aberrationen höherer Ordnung mit unterschiedlichen Refraktionsschwankungen über den Tag einhergehen und verursachen ein schlechteres Sehen in den ersten Tagen nach dem Absetzen der Linsen.…”
Section: Interventionen Zur Progressionsminderungunclassified